Effects of Chemical Compounds on the Activity of the N‐acetyl‐β‐D‐Glucosaminidase of the Marine Prawn, Palaemon serratus: Screening In Vitro. (27th February 2023) - Rollin, Marc; Coulaud, Romain; Rocher, Béatrice; Billoir, Elise; Geffard, Olivier; Duflot, Aurélie; Fromont, Chloé; Boulangé‐Lecomte, Céline; Le Foll, Frank; Xuereb, Benoit
Abstract: N‐acetyl‐β‐D‐glucosaminidase (NAGase) is important for crustaceans because the enzyme activity is necessary for the molting process. The present study aimed to assess the sensitivity of Palaemon serratus NAGase activity to a set of compounds of diverse chemical families in the context of in vitro exposures. Compounds representing different chemical families were selected according to their abundance, impact in the environment, and relevance as disruptors of the molting process. In a first step, four solvents (dimethylsulfoxide [DMSO], methanol, acetone, and ethanol) were tested to determine their suitability to dissolve hydrophobic compounds without affecting NAGase activity. Exclusively, ethanol had no effect on enzyme activity and on the integrity of the proteins present in the enzyme extract. The 18 other compounds were tested and four of these compounds, pentoxifylline, fenoxycarb, dithiocarbamate, and RH5849, showed a specific alteration on the activity of NAGase, without affecting the protein content. However, cadmium, zinc, and glyphosate showed a nonspecific alteration, affecting both the enzyme activity and the proteins, whereas ibuprofen exclusively altered the protein content. Finally, 10 of the 22 tested compounds (including DMSO, acetone, and methanol) showed a direct alteration of NAGase activity. Environ Toxicol Chem 2023;42:846–858. © 2023 SETAC